The perception of the population that captures mussels and barnacles at easter on measures of ecosystem conservation - Jeremias, Maria (2016)
The perception of the population that captures mussels (Mytilus galloprovincialis) and barnacles (Pollicipes pollicipes) on Holy Friday on the campaign launched by the Cascais city council (“At Easter the one who pays is the mussel”) to prevent the depletion of the stocks and their opinion on the need of preservation of these two species and biodiversity in intertidal area. To evaluate it we went to the area where the campaign was launched and made a questionnaire to each family, in a total of 62 surveys. This activity is mainly carried out by men between the ages of 30 and 60 years old. 62% of the pickers came from different areas of the council, 30% come from neighbouring councils and the other 8 % from distant places. The results confirm that the capture is mainly done at Easter (82%). 41% of the people inquired collect mussels, 16% collect barnacles and 43% collect both species. The majority of the pickers knows the maximum weight allowed to capture mussels but doesn’t know it about barnacles and less than half of the people answer correctly about the minimum length of the mussel shell. 94% state that the capture is done to private consumption. The perception of the people about the need of conservation of both species and biodiversity in intertidal is above 70%. As far as the campaign is concerned, people, in general, agree with it but their answers are not consensual: some said it is very good (40%) while others said that it is very bad (47%). About the reinforced surveillance done during this day by the Maritime and the City Council Police almost everybody said that it may end up with this tradition.